HISTORIAN’S WORKSHOP: ¿POSITIVISM OR A NEW PARADIGM? - Barros, Carlos (2014)
In this paper we try to sum up new and international trends and debates, using a transatlantic and Latin point of view, about methods, historiography, theories and relationship between historians and society in the 21st century. Using the preamble of the History under Debate Manifesto (2001) and using the most recent debates in HaD in social networks as well, as starting point, we analyse the polarization of the historians between the ones who think that we need new paradigms without forget the avant-garde of the 20th century, and the ones who want the return of the positivism and the postmodernism. This is a historiographic withdrawal that we study through the sentences, methods and clichés said and done inside and out of the classes and offices. Digital and oral data seem to demonstrate, inasmuch as Ranke’s return, an important homogeneity between the different fields, Universities and countries.